»Att leva ut slaven i mig«: Postkoloniala perspektiv på Sara Lidman i apartheids Sydafrika 1960–1961 - Granqvist, Raoul J. (Tidskrift för litteraturvetenskap, 2009)
Postcolonial Perspectives on Sara Lidman’s Writings from South Africa 1960–1961 The Swedish writer Sara Lidman (1923–2004) wrote Jag och min son (I and My Son) after a brief stint in apartheid’s South Africa in 1960–1961, from where she was expelled for a violation of the Immorality Act. Based on a close, interrelated study of her diary, her letters and the two manuscripts (first published in 1961 and revised and re-published in 1963), this essay (»’To outlive the slave in me’: Postcolonial Perspectives on Sara Lidman in Apartheid’s South Africa 1960–1961«) examines the colonial boundary crisis of the Self. The major protagonists in the novel(s) embody variously aspects of the writer’s angst as it developed in the Johannesburg colonial setting of persecuted ANC members, the elite of the local Swedish community, and the pressure of her anticolonial frustrations. Sexuality is a major element in the »nervous condition« that characterizes the fragmented and confusing conceptualization of the novel. Its extensive rewriting was an attempt at strengthening its ideological, anti-imperial modus, pushing the novel into the environs of the postcolonial allegory such as in such texts as Jean Rhys’ Wide Sargasso Sea (1966), Tsitsi Dangarembga’s Nervous Conditions (1988) and Bessie Head’s A Question of Power (1974). A second self-castigating theme, this essay claims, is the impact of the religious background of the author as born into – but never at peace with – strong evangelical and paternal practices. »Outliving the slave« (a quote from one of her letters) in the title of the essay proposes a Fanonian reading of the circulatory and traumatizing notion of rebellion (against Apartheid) and submission (to it). The third theme involves the idealization of the child that also involves a colonial cul-desac of self-positioning expressed both in the novel and the writer’s attempts at adopting an African child (never realized).